D4.6 Material from 3rd workshop - Hadjimitsis, Diofantos G.; Christofe, Andreas; Agapiou, Athos; Lysandrou, Vasiliki; Jaspersen, Verena (My University, 2018)
The present deliverable summarizes the outcomes of the third ATHENA workshop and provides all related material, both prior its accomplishment (e.g. agenda) and material such as presentations and list of participants. The third workshop was entitled: “Geo information systems (GIS)” and was organised by Verena Jaspersen from the DLR at the RSCy 2018 in Cyprus. The workshop was split into two parts. In the first part, Verena Jaspersen covered the fundamentals of GIS in form of a presentation. What is GIS? What is it used for? What are the main parts of a GIS? Which software can be used to set up a GIS? Furthermore, the participants got an insight into examples of web-based GIS that show-case how GIS can be used to disseminate data and information to a wide user group. The participants also learnt about Open Geospatial Consortium and their standards such as Web Mapping Service (WMS) and Catalogue Service for the Web (CSW) to make GIS work in a distributed world. The second part was a real Hands-On Workshop on working with. In this hands-on workshop the participants started to work with QGIS (https://www.qgis.org). After a general introduction to QGis and its plugin mechanism, we practically worked with what was covered during the presentation.
Keywords: ATHENA project; Geo information systems; Open Geospatial Consortium; Web Mapping Service; Catalogue Service for the Web